Arabidopsis root growth and development under metal exposure presented in an adverse outcome pathway framework. (17th July 2021) - van Dijk, Jesper R.; Kranchev, Mario; Blust, Ronny; Cuypers, Ann; Vissenberg, Kris
Abstract: Due to human activities, soils become more and more polluted with metals, which imposes risks for human health and wildlife welfare. As most of the metals end up in the food chain through accumulation in plants, we need to establish science‐based environmental criteria and risk management policies. To meet these necessities, a thorough understanding is required of how these metals accumulate in and affect plants. Many studies have been conducted towards this aim, but strikingly, only a few entries can be found in ecotoxicological databases, especially on Arabidopsis thaliana, which serves as a model species for plant (cell) physiology and genetic studies. As experimental conditions seem to vary considerably throughout literature, extrapolation or comparison of data is rather difficult or should be approached with caution. Furthermore, metal‐polluted soils often contain more than one metal, yet limited studies investigated the impact of metal mixtures on plants. This review aims to compile all data concerning root system architecture under Cu, Cd and Zn stress, in single or multi‐metal exposure in A. thaliana, and link it to metal‐induced responses at different biological levels. Global incorporation into an adverse outcome pathway framework is presented. Abstract : This review compiles all data on root system architecture under Cu, Cd and Zn, in single or multi‐metal exposure in Arabidopsis thaliana, and links it to the responses at different biological levels. Global incorporation of the data into an adverse outcome pathway framework is presented.